ANALYSIS OF DIFFERENTIATED LEARNING OF PANCASILA EDUCATION SUBJECTS AT UPT SPF SMP NEGERI 3 MAKASSAR - Muhlis, Muhlis; Hasnawi, Hasnawi Haris; Imam, Imam Suyitno; Najamuddin, Najamuddin (PT. Jurnal Center Indonesia Publisher, 2025)
In the implementation of the Independent Curriculum, we recognize the existence of a differentiated learning approach. Differentiated learning is a process of different learning treatments, both in terms of content, process, and product carried out by teachers according to the level of readiness, needs, and learning styles of each student. This study aims to analyze how Pancasila education subject teachers prepare and implement differentiated learning at the UPT SPF SMP Negeri 3 Makassar. The number of informants in this study was 5 people consisting of 3 key informants and 2 additional informants. The data collection technique was by conducting observations, interviews and documentation. This research is a descriptive Qualitative study. The results of this study indicate that the way Pancasila education teachers prepare differentiated learning is: 1.1.) Making questions, compiling or preparing initial assessment instruments; 1.2.) Carrying out and analyzing initial assessments; and 1.3.) Making teaching modules. 2) The process of implementing differentiated learning is carried out by Pancasila education teachers, namely: 2.1.) Mapping or forming groups of students based on the results of the initial assessment; and 2.1.) Carrying out the differentiated learning process in terms of content, process, and product.